The impact of State-Of-Rivers Reporting on people’s attitudes towards river conservation : a case study of the Buffalo and Hartenbos & Klein Brak Catchments in South Africa - Strydom, Wilma Fernanda (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.